Effect of intravitreal hyaluronidase on the clearance of tritiated water from the vitreous to the choroid. Issue 7 (July 1985) - Foulds, W S; Allan, D; Moseley, H; Kyle, P M
Abstract : The rate of transfer of intravitreally injected tritiated water from the mid vitreous to the choroid is significantly increased after depolymerization of vitreous hyaluronic acid by injected hyaluronidase. The significance of this finding is discussed in relation to such conditions as retinal detachment and reattachment.